2018
DOI: 10.1194/jlr.m084723
|View full text |Cite
|
Sign up to set email alerts
|

Carboxamido steroids inhibit the opening properties of transient receptor potential ion channels by lipid raft modulation

Abstract: Transient Receptor Potential (TRP) cation channels, like the TRP Vanilloid 1 (TRPV1) and TRP Ankyrin 1 (TRPA1), are expressed on primary sensory neurons. These thermosensor channels play a role in pain processing. We have provided evidence previously that lipid raft disruption influenced the TRP channel activation, and a carboxamido-steroid compound (C1) inhibited TRPV1 activation. Therefore, our aim was to investigate whether this compound exerts its effect through lipid raft disruption and the steroid backbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 76 publications
7
33
0
Order By: Relevance
“…Both compounds had inhibitory action on formalin-evoked acute neurogenic inflammatory nocifensive reactions (paw liftings, lickings, holdings, and shakings) in the second, neurogenic inflammatory phase by 36 and 51%, respectively. These novel in vivo results are well supported by our previous in vitro findings showing that C1 and MCD significantly and concentration-dependently inhibit TRPV1 and TRPA1 receptor activation both on primary sensory neuronal cultures and receptor-expressing cell line (Szőke et al, 2010;Szánti-Pintér et al, 2015;Sághy et al, 2015Sághy et al, , 2018. We have previously proved by filipin staining and fluorescence spectroscopy that C1 similarly to MCD depleted cholesterol from the plasma membrane of sensory neurons, and therefore, they are both considered to be lipid raft disruptors (Sághy et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Both compounds had inhibitory action on formalin-evoked acute neurogenic inflammatory nocifensive reactions (paw liftings, lickings, holdings, and shakings) in the second, neurogenic inflammatory phase by 36 and 51%, respectively. These novel in vivo results are well supported by our previous in vitro findings showing that C1 and MCD significantly and concentration-dependently inhibit TRPV1 and TRPA1 receptor activation both on primary sensory neuronal cultures and receptor-expressing cell line (Szőke et al, 2010;Szánti-Pintér et al, 2015;Sághy et al, 2015Sághy et al, , 2018. We have previously proved by filipin staining and fluorescence spectroscopy that C1 similarly to MCD depleted cholesterol from the plasma membrane of sensory neurons, and therefore, they are both considered to be lipid raft disruptors (Sághy et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, we provided the first evidence and the presence and the position of the carboxamido group was important for this action mediated by cholesterol depletion from the plasma membrane. This effect was similar to that of MCD, but in a much lower, 1000-fold concentration (Szánti-Pintér et al, 2015;Sághy et al, 2018).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Recently, it was reported that carboxamide steroids (synthetic compounds) inhibit the opening of TRPV1 and TRPA1 and that this negative regulation is through disruption of the lipid rafts [187]. Although this last study does not assess changes in the temperature threshold of activation of these channels, it will be interesting to evaluate this possibility.…”
Section: The Relationship Between the Thermal Threshold Of Trp Channementioning
confidence: 95%
“…Most often channel activity is suppressed by cholesterol enrichment or enhanced by cholesterol depletion of the membrane, as was observed for several K + channels 8,[10][11][12][13][14] , voltage-gated Na + channels 15 , as well as volume-regulated anion channels 16 . In some other channels, however, the opposite was reported: depletion of membrane cholesterol inhibited epithelial Na + channels (eNaC) 17 and transient receptor potential (Trp) channels 18,19 . Based on the conclusions of these studies two possible mechanisms have emerged to explain cholesterol effects on channel gating: specific interaction with the channel via a binding site; or an indirect effect through changes in the physical parameters of the membrane (e.g.…”
Section: Introductionmentioning
confidence: 99%